Consciousness and Moral Status - Shepherd, Joshua (Routledge Focus on Philosophy, 2018)
In this book Joshua Shepherd presents a systematic account of the value present within conscious experience. This account emphasizes not only the nature of consciousness, but also the importance of items within experience such as affect, valence, and the complex overall shape of particular valuable experiences. Shepherd also relates this account to difficult cases involving non-humans and humans with disorders of consciousness, arguing that the value of consciousness influences and partially explains the degree of moral status a being possesses, without fully determining it. The upshot is a deeper understanding of both the moral importance of phenomenal consciousness and its relations to moral status. This book will be of great interest to philosophers and students of ethics, bioethics, philosophy of psychology, philosophy of mind, and cognitive science.